Real‐Life Turning Movements Capture Subtle Longitudinal and Preataxic Changes in Cerebellar Ataxia. Issue 5 (24th January 2022) - Thierfelder, Annika; Seemann, Jens; John, Natalie; Harmuth, Florian; Giese, Martin; Schüle, Rebecca; Schöls, Ludger; Timmann, Dagmar; Synofzik, Matthis; Ilg, Winfried
Abstract: Background: Clinical and regulatory acceptance of upcoming molecular treatments in degenerative ataxias might greatly benefit from ecologically valid endpoints that capture change in ataxia severity in patients' real life. Objectives: This longitudinal study aimed to unravel quantitative motor biomarkers in degenerative ataxias in real‐life turning movements that are sensitive for changes both longitudinally and at the preataxic stage. Methods: Combined cross‐sectional (n = 30) and longitudinal (n = 14, 1‐year interval) observational study in degenerative cerebellar disease (including eight preataxic mutation carriers) compared to 23 healthy controls. Turning movements were assessed by three body‐worn inertial sensors in three conditions: (1) instructed laboratory assessment, (2) supervised free walking, and (3) unsupervised real‐life movements. Results: Measures that quantified dynamic balance during turning—lateral velocity change (LVC) and outward acceleration—but not general turning measures such as speed, allowed differentiating ataxic against healthy subjects in real life (effect size δ = 0.68), with LVC also differentiating preataxic against healthy subjects (δ = 0.53). LVC was highly correlated with clinical ataxia severity (scale for the assessment and rating of ataxia [SARA] score, effect size ρ = 0.79) and patient reported balance confidence (activity‐specific balance confidence scale [ABC] score, ρ = 0.66). Moreover, LVC in real life—but not general turning measures or the SARA score—allowed detecting significant longitudinal change in 1‐year follow‐up with high effect size ( r prb = 0.66). Conclusions: Measures of turning allow capturing specific changes of dynamic balance in degenerative ataxia in real life, with high sensitivity to longitudinal differences in ataxia severity and to the preataxic stage. They thus present promising ecologically valid motor biomarkers, even in the highly treatment‐relevant early stages of degenerative cerebellar disease. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society